2014
DOI: 10.4274/jcrpe.1233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel ROR2 Gene Mutations in Indian Children with Robinow Syndrome

Abstract: Ob­jec­ti­ve: Robinow syndrome (RS) is an extremely rare genetic disorder characterized by short-limbed dwarfism, defects in vertebral segmentation and abnormalities in the head, face and external genitalia. Mutations in the ROR2 gene cause autosomal recessive RS (RRS) whereas mutations in WNT5A are responsible for the autosomal dominant (AD) form of RS. In AD Robinow patients, oral manifestations are more prominent, while hemivertebrae and scoliosis rarely occur and facial abnormalities tend to be milder.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(30 reference statements)
1
13
0
Order By: Relevance
“…Over 100 cases of RS have been reported to date, with an incidence of 1:500,000 with no sex preference [Tamhankar et al, ]. Autosomal recessive RS had been described in patients from various ethnic groups [Nazer et al, ; Balci et al, ; Aksit et al, ; Afzal et al, ; Kulkarni and Reddy, ; Mazzeu et al, ; Mehawej et al, ; Tamhankar et al, ]. Although, molecular studies were reported only in one Egyptian family with ARRS [Ali et al, ], other previous reports suggested AR inheritance in Egyptian patients with RS [El‐Ruby et al, ; Meguid and Aglan, ; Temtamy et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over 100 cases of RS have been reported to date, with an incidence of 1:500,000 with no sex preference [Tamhankar et al, ]. Autosomal recessive RS had been described in patients from various ethnic groups [Nazer et al, ; Balci et al, ; Aksit et al, ; Afzal et al, ; Kulkarni and Reddy, ; Mazzeu et al, ; Mehawej et al, ; Tamhankar et al, ]. Although, molecular studies were reported only in one Egyptian family with ARRS [Ali et al, ], other previous reports suggested AR inheritance in Egyptian patients with RS [El‐Ruby et al, ; Meguid and Aglan, ; Temtamy et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Three of our patients had ASD and PS while one patient had VSD. Among the abnormalities reported are bicuspid aortic valve, tetralogy of Fallot, ASD, VSD, and coarctation of aorta, but the commonest appears to be PS [Patton and Afzal, ; Tamhankar et al, ]. El‐Ruby et al [], in their report of the first Egyptian patients with RS, described dextrocardia in one patient and PS in two other patients with RS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutated gene responsible for RRS has been identified as ROR2 at 9q22, a member of the receptor tyrosine kinase-like gene family that encodes an orphan membrane-bound tyrosine kinase involved in cell growth and differentiation [6][7][8]. Mutations in WNT5A, locus 3p 14.3 are responsible for the DRS which is characterized by more prominent oral manifestations [4].…”
Section: Discussionmentioning
confidence: 99%
“…The important role of genetic testing by the knowledge about the molecular basis of the disorder enabled us to make a prenatal diagnosis, genetic carrier detection and proper genetic counselling for families [6]. …”
Section: Genetic Testingmentioning
confidence: 99%